Reducing effects of design uncertainties on product sustainability. Issue 1 (31st December 2016) - Afshari, Hamid; Peng, Qingjin; Gu, Peihua
Abstract: Product designers need to consider users' requirement changes in the product life cycle. Existing practices of product design lack an effective method to quantify uncertainty effects on products. This research proposes a method to evaluate product sustainability under the generational variety uncertainty. An integrated method of agent-based modeling, quality function deployment (QFD), and axiomatic design theory is developed to simulate users' preference changes. The contribution in this paper is to address all sustainability pillars including the social, environmental, and economy in the proposed solution. The quantified uncertainty is then used to evaluate impacts on product sustainability. The proposed method is validated using an example of the wheelchair design.